Integrated factor analysis and fuzzy analytic network process (FANP) model for supplier selection based on supply chain risk factors - Sinrat, S.; Atthirawong, W. (My University, 2015)
Currently, the supply chain management is an important part of several organizations. The risk in supply chain is a potential variation of outcomes which decreases the efficiency in operations. The supplier selection is one of the most critical functions to the success of a manufacturing firm. The objective of this study was to develop the supplier evaluation in supply chain risk approach based on an integrated factor analysis and Fuzzy Analytic Network Process (FANP) model. The model has applied to an electrical and electronic industry in Thailand. The framework of this study had two main thoughts. The first part was to investigate supply chain risk factors from data collection via questionnaire. The questionnaire was answered by 225 respondents in electrical and electronic companies in Thailand. By means of the statistical technique of factor analysis, it was revealed that supply chain risk factors can be categorized into six factors and thirty sub-factors. The second part was to develop a mathematical model for supplier selection decisions via using FANP by incorporating supply chain risk factors acquired from the first part. A detailed step by step implementation method for determining fuzzy scales and calculating weights factors and sub-factors were discussed and finally issues prioritize risk value for alternative best supplier were also mentioned.
Keywords: Analytic network process; Factor analysis; Fuzzy; Supply chain risk factors; Upplier selection